2006
DOI: 10.1111/j.1365-2958.2006.05160.x
|View full text |Cite
|
Sign up to set email alerts
|

IscR‐dependent gene expression links iron‐sulphur cluster assembly to the control of O2‐regulated genes in Escherichia coli

Abstract: SummaryIscR is an iron-sulphur (Fe-S) cluster-containing transcription factor that represses transcription of the operon containing its own gene and the iscSUAhscBA-fdx genes, whose products are involved in Fe-S cluster biogenesis. In this study, global transcriptional profiling of Escherichia coli IscR + and IscR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
391
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(409 citation statements)
references
References 64 publications
14
391
0
4
Order By: Relevance
“…The enzyme is synthesized under anaerobic conditions, and its expression is switched off in a fully oxic environment (36)(37)(38). A coexpressed cytochrome bd-II oxidase (39) is thought to complete this short respiratory electron transport chain between H 2 and O 2 under microaerobic conditions.…”
Section: Assay Of Intermolecular Electron-transfer Kinetics Using Cytmentioning
confidence: 99%
“…The enzyme is synthesized under anaerobic conditions, and its expression is switched off in a fully oxic environment (36)(37)(38). A coexpressed cytochrome bd-II oxidase (39) is thought to complete this short respiratory electron transport chain between H 2 and O 2 under microaerobic conditions.…”
Section: Assay Of Intermolecular Electron-transfer Kinetics Using Cytmentioning
confidence: 99%
“…Although direct binding of RirA to DNA has not been reported, a DNA sequence necessary for RirA-dependent regulation was identified (63,64,75). The ligand that imparts iron responsiveness to RirA has not been established, although the related Rrf2-type protein IscR binds and responds to Fe-S clusters, and it has been suggested that RirA also binds Fe-S clusters (19,31,58). Agrobacterium tumefaciens is also a well-studied member of the Alphaproteobacteria, related to both B. japonicum and R. leguminosarum (7,53).…”
mentioning
confidence: 99%
“…For example, IscR of E. coli binds to a slight upstream of 235 sequence and induces expression of some target genes, while it also binds to a site partly overlapped with 210 sequence and represses expression of other target genes (Giel et al, 2006). Our data revealed that the Slr0846-binding sequence is located more than 150 bp upstream from the transcription start point P1 in the psaA-6/5 region, although the precise binding motif has not yet been elucidated.…”
Section: The Mechanism Of Transcriptional Activation By Slr0846mentioning
confidence: 87%